Autoimmune pancreatitis masquerading as carcinoma head of pancreas: A case report and review of literature. (September 2019) - Gill, Meenu; Brar, Komal; Godara, Rajesh; Bhargava, Shilpi; Sachdeva, Bhawna; Sen, Rajeev; Jain, Promil
Abstract: Introduction: Autoimmune pancreatitis (AIP) is a rare form of chronic inflammatory pancreatic disease secondary to an underlying autoimmune mechanism. It is now considered as pancreatic manifestation of IgG4 related disease, which is a multisystem disease. Case report: We are reporting a patient who presented with obstructive jaundice and mass head of pancreas on Computed Tomography (CT) scan. Considering a strong clinical suspicion of pancreatic cancer, Whipple procedure was done. Histopathological report revealed intense lymphoplasmacytic infiltrate and fibrosis with collagenisation, so possibility of AIP was suggested. Serum IgG4 levels were advised and found to be increased. Diagnosis of AIP was made and patient responded to steroids. Discussion: Pre-operative core biopsy of the pancreas and Serum IgG4 levels are sufficient to make the diagnosis and resection is usually not recommended in AIP. Conclusion: Awareness of the entity and use of ancillary techniques in making the pre-operative diagnosis could have saved the patient from an extensive surgical procedure. Highlights: Autoimmune Pancreatitis is a pancreatic manifestation of IgG4 related disorders. It can clinically and radiologically present as pancreatic malignancy. Resection is not required in Autoimmune Pancreatitis. Pre-operative investigations can save the patient from morbidity due to Whipples. Whipples procedure is undesired in these patients. This entity should be kept in mind while dealing with mass lesions in head of pancreas.